2009
DOI: 10.1158/1535-7163.mct-08-0944
|View full text |Cite
|
Sign up to set email alerts
|

Targeting both HIF-1 and HIF-2 in human colon cancer cells improves tumor response to sunitinib treatment

Abstract: Sunitinib is an oral small-molecule multitargeted receptor tyrosine kinase inhibitor that has recently been shown to have clinical benefit as a single agent in renal cell cancer and gastrointestinal stromal tumors, leading to its Food and Drug Administration approval for treatment of these cancers. However, the benefit is short-lived; and for the majority of cancers, sunitinib single-agent clinical activity is low. Therefore, combination strategies with sunitinib are currently in clinical development. The hypo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 45 publications
(55 reference statements)
0
49
0
Order By: Relevance
“…HIF-2α promotes hypoxic tumor cell proliferation by enhancing c-myc transcriptional activity (22) and results in CRC progression by dysregulating iron homeostasis (23). Disruption of the HIF-2α gene inhibits tumor angiogenesis and perfusion in human colon cancer cells (24). In the present study, overexpression of miR-185 suppressed proliferation and invasion, and reduced expression levels of HIF-2α in colon cancer cells, suggesting that miR-185 may be implicated in the development of colon cancer cells through inhibition of the HIF-2α pathway.…”
Section: Discussionmentioning
confidence: 99%
“…HIF-2α promotes hypoxic tumor cell proliferation by enhancing c-myc transcriptional activity (22) and results in CRC progression by dysregulating iron homeostasis (23). Disruption of the HIF-2α gene inhibits tumor angiogenesis and perfusion in human colon cancer cells (24). In the present study, overexpression of miR-185 suppressed proliferation and invasion, and reduced expression levels of HIF-2α in colon cancer cells, suggesting that miR-185 may be implicated in the development of colon cancer cells through inhibition of the HIF-2α pathway.…”
Section: Discussionmentioning
confidence: 99%
“…HIF-3 lacks structures for transactivation existed in the C-termini of HIF-1 and HIF-2 . HIF-2 might contribute to tumor angiogenesis in some cells (Burkitt et al, 2009;Favier et al, 2007;Giatromanolaki et al, 2006). However regulation of HIF-2 or HIF-3 by miRNAs has not reported yet.…”
Section: Hif-2α and Hif-3αmentioning
confidence: 99%
“…123 Burkitt et al at the University of Michigan Comprehensive Cancer Center demonstrated that genetic disruption of both HIF-1a and HIF-2a had synergistic anti-tumour activity when combined with sunitinib in a colorectal xenograft model. 124 Clinically, Kummar et al at the NCI demonstrated that metronomic dosing of TPT inhibited HIF-1a in patients, and that correlated with antiangiogenics as well, as measured by decreased tumour expression of VEGF and decreased tumour blood flow and permeability. These data validate extensive preclinical data showing that metronomic TOP1 inhibition can inhibit HIF-1a and important downstream targets of HIF-1.…”
Section: Combination Therapymentioning
confidence: 99%